LITERASI DAN NUMERASI KAMPUS MENGAJAR ANGKATAN 4 PADA SMP MUHAMMADIYAH PAREPARE - Masnur Masnur; Irmayani Irmayani; Andi Wafiah; Syahirun Alam; Nur Ilmi; Muhammad Jabir; Farhan Dzulkhair Hasan; Ferdiansyah Saing; Selmianti Selmianti; Misbahuddin Misbahuddin; Muhammad Iqbal Putra; Hendro Widarto; Hamka Hamka; Dian Wahyudi (Gapenas Publisher, 2023)
The teaching campus program is one of the flagship programs of the Ministry of Education, Culture, Research and Technology's Free Learning Campus (MBKM) policy. The Teaching Campus Program is a program that provides opportunities for students to learn outside the classroom by becoming partners with teachers in the learning process at the basic education level. The Teaching Campus Program is a collaboration whose beneficiaries are students at elementary and middle school levels of education. This program focuses on two outcomes, namely developing the competency of students participating in the program through increasing leadership capacity, creativity and innovation, problem solving, communication, team management, and improving analytical thinking, as well as increasing literacy and numeracy for students at target schools. The Class 4 Teaching Campus Program is implemented at Muhammadiyah Parepare Middle School, which is located at Jl. Muhammadiyah No. 8, District. Soreang, Parepare City, South Sulawesi. In the Class 4 Teaching Campus program at SMP Muhammadiyah Parepare, the forms of assistance provided by students in terms of teaching include students helping to teach offline, providing special guidance to students who are not very fluent in reading. In school administration assistance, namely improving library administration, including making visitor lists and book borrowing lists and arranging books. Technology adaptation assistance includes the introduction of computer devices and also guidance in using several learning media applications such as Microsoft Word, Canva and Google Meeting.